Endogenous nitric oxide and hydrogen peroxide detection in indole-3-butyric acid-induced adventitious root formation in Camellia sinensis - Kang WEI; Li-yuan WANG; Li RUAN; Cheng-cai ZHANG; Li-yun WU; Hai-lin LI; Hao CHENG (Journal of Integrative Agriculture, 2018)
Nitric oxide (NO) and hydrogen peroxide (H2O2) are essential signaling molecules with key roles in auxin induced adventitious root formation in many plants. However, whether they are the sole determinants for adventitious root formation is worth further study. In this study, endogenous NO and H2O2 were monitored in tea cutting with or without indole-3-butyric acid (IBA) treatment by using the fluorescent probes diaminofluorescein diacetate (DAF-2DA) and 2',7'-dichlorodihydrofluorescein diacetate (DCF-DA), respectively. The overproduction of NO and H2O2 was detected in the rooting parts of tea cuttings treated with or without IBA. But little NO and H2O2 was detected before the initiation phase of tea cuttings even with IBA treatment indicating that they might be not directly induced by IBA. Further carbon and nitrogen analysis found that the overproduction of NO and H2O2 were coincident with the consumption of soluble sugars and the assimilation of nitrogen. These results suggest that rooting phases should be taken into consideration with the hypothesis that auxin induces adventitious root formation via NO- and H2O2-dependent pathways and sink establishment might be a prerequisite for NO and H2O2 mediated adventitious root formation.